Contra o Racismo Mobilização para a mudança social na América Latina - Moreno Figueroa, Monica Gabriela (Latin America Research Commons, 2023)
Powerful narratives describe Latin American nations as fundamentally mestizo. These narratives have made it difficult to recognize racism in the region, but recent multiculturalist turns have increased recognition of black and indigenous cultures and identities. Multiculturalism can focus on issues of identity and visibility and address unconcerned forms of racism, but it can also divert attention from structural racism and racialized inequality, and thus constrain broader anti-racist initiatives. In addition, multiple understandings of how racism and anti-racism are inserted in projects of social transformation make racism a complex and multifaceted issue. The seven essays in Contra oracismo investigate actors in Brazil, Colombia, Ecuador and Mexico who go beyond the politics of recognition to address structural inequalities and build common ground with other marginalized groups. The organizations in this study advocate an approach to social structural transformation that promotes alliances, is inclusive, and is inspired by a radical imagination.